Sales Blitz Marketing Communication Strategy in Increasing Revenue at Horison Hotel Pekalongan - Dewi Maria, Aletta; Susmono Widagdo, Chrisostomus; Fajar Pradapa, Sri Yulianto; Maskur, Ali (Faculty of Law, Universitas Pekalongan, 2024)
The company's marketing efforts influence sales growth in the hotel service lodging industry in addition to the caliber of the products. For instance, the company should implement an appropriate marketing plan because of the intense competition. The sales blitz is a key component of the marketing plan to boost Hotel Horison Pekalongan's revenue. The sales blitz team needs to be improved once more due to the volume of new competitors. This thesis aims to explain the Blitz sales marketing communication technique used to boost revenue at the Horison Hotel Pekalongan. Also, describe the challenges and how to conduct a successful sales campaign. It is anticipated that sales will rise due to the sales blitz events. The author interviewed people in the marketing industry, specifically sales executives and managers.